MAIN DIRECTIONS OF TRANSFORMATION OF UZBEKISTAN'S ECONOMIC SECTORS IN THE CONTEXT OF THE DIGITAL ECONOMY (Universal International Scientific Journal, 2026)
The issue of transforming national economic sectors in the digital economy is of great importance for ensuring sustainable economic growth and increasing competitiveness. The introduction of digital technologies serves to modernize production processes, improve management systems, and increase economic efficiency. In particular, the use of digital solutions in industry, agriculture, the service sector, and the financial system is taking economic activity to a new level. This article analyzes the main directions of transforming economic sectors of Uzbekistan in the digital economy, the state of implementation of digital technologies, and their impact on economic efficiency. It also examines economic, organizational, and institutional factors affecting the acceleration of digital transformation. The results of the study serve to develop practical recommendations for further developing digitalization processes in economic sectors and increasing their efficiency.
Keywords: digital economy; digital transformation; economic sectors